2006
DOI: 10.1093/jxb/erj118
|View full text |Cite
|
Sign up to set email alerts
|

A root-specific bZIP transcription factor is responsive to water deficit stress in tepary bean (Phaseolus acutifolius) and common bean (P. vulgaris)

Abstract: Root cDNA libraries were differentially screened to isolate water deficit-responsive transcripts in the relatively drought-resistant plant tepary bean (Phaseolus acutifolius). A novel root-specific, water deficit-responsive transcript was identified and predicted to encode a bZIP transcription factor. The orthologous form of this gene was isolated from the drought-sensitive P. vulgaris and the patterns of expression of these genes compared. These genes have predicted amino acid sequences in the bZIP domain tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
60
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 29 publications
1
60
0
Order By: Relevance
“…They include various transcription factors, protein kinases, protein phosphatases, response regulators, calmodulin-like protein, and ABI binding protein amongst others. bHLH, bZIP, EREBP, NAC, MPK7, ABI, GASA4, and CAM proteins are examples of signal transduction elements or transcription factor families that have been found to be responsive to drought stress in other species (ToledoOrtiz et al 2003;White and Broadley 2003;Rodriguez-Uribe and O'Connell 2006;Shen et al 2003;Olsen et al 2005;Meng et al 2009a, b). As expected, these gene families were also identified in our study, where not only families but homologs from the same family demonstrated unique expressional changes in response to water scarcity.…”
Section: Discussionmentioning
confidence: 99%
“…They include various transcription factors, protein kinases, protein phosphatases, response regulators, calmodulin-like protein, and ABI binding protein amongst others. bHLH, bZIP, EREBP, NAC, MPK7, ABI, GASA4, and CAM proteins are examples of signal transduction elements or transcription factor families that have been found to be responsive to drought stress in other species (ToledoOrtiz et al 2003;White and Broadley 2003;Rodriguez-Uribe and O'Connell 2006;Shen et al 2003;Olsen et al 2005;Meng et al 2009a, b). As expected, these gene families were also identified in our study, where not only families but homologs from the same family demonstrated unique expressional changes in response to water scarcity.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA (10 or 20 lg) was digested separately with AvaI, BamHI, EcoRI, EcoRV, HindIII, PstI or XbaI; blots were prepared, hybridized and washed as described (Rodriguez-Uribe and O'Connell 2006). Probes for hybridization were prepared using cloned mtDNA genes: wheat for cox1, cotton for cox2 and cox3 (Wang 2008), maize for atp1 (atpA) (Braun and Levings 1985), atp6 (Dewey et al 1986), cob and rrn26 (26S rRNA) (Stern et al 1982), and petunia for atp9 (Young and Hanson 1987).…”
Section: Southern Blot Analysismentioning
confidence: 99%
“…In plants, like other transcription factor genes, members of the bZIP transcription factor family are also either expressed constitutively or in an organ-specific (Schindler et al, 1992a;Rodriguez-Uribe and O'Connell, 2006), stimulus-responsive (de Vetten and Ferl, 1995), development-dependent (Chern et al, 1996), and cellcycle-specific (Minami et al, 1993) manner. So far, over 120 bZIP transcription factors have been identified in different plants (Supplemental Table S1).…”
mentioning
confidence: 99%